Agent and Broker Intermediaries in Insurance Markets – An Empirical Analysis of Market Outcomes - Martina Eckardt (Universität Rostock, Institut für Volkswirtschaftslehre, 2002)
Insurance markets are characterized by profound market imperfections. Insurance intermediaries reduce transaction costs and information asymmetries. From transaction cost economics, agency theory, and law and economics literature the hypothesis is derived that insurance brokers may provide more high-quality information and advisory services which are better suited for the needs of the consumers than insurance agents. Empirical tests for German insurance intermediaries confirm this thesis. But there are also findings that structural factors like firm size, employment structure and degree of specialization may outweigh the incentives set by different legal settings.
Keywords: D82; G14; G22; L15; 330; Versicherungsmarkt; Versicherungsvermittlung; Versicherungsökonomik; Schätzung; Deutschland; Markteffizienz